Current trends in hydrogen production, storage and applications in India: A review. (October 2022) - Qureshi, Fazil; Yusuf, Mohammad; Kamyab, Hesam; Zaidi, Sadaf; Junaid Khalil, Mohd; Arham Khan, Mohd; Azad Alam, Mohammad; Masood, Faisal; Bazli, Leila; Chelliapan, Shreeshivadasan; Abdullah, Bawadi
Graphical abstract: Highlights: Recent trends in H2 production, storage, and applications in India. Steam reforming of methane still the major source of H2 production (48%). H2 application in mild-HEVs are best amongst the existing designed vehicles. H2 storage as metal hydrides is the safest technique due to its stability. Future outlook of potential hydrogen economy in India. Abstract: With the increase in world population, the corresponding energy demand is also rising at a fast pace. The exploitation and usage of fossil fuels in transportation and energy generation is increasing the concentration of global greenhouse gases (GHGs) and polluting the environment. To achieve pledges of the 'Paris Agreement' and check global warming, there is a crucial need to reduce our dependence on fossil fuels and switch to cleaner and greener fuel sources. Hydrogen is a clean fuel since its exhaust is only water after combustion. Hydrogen may be a promising alternative to fossil fuels due to its high calorific value. However, there are still several hurdles and challenges in the commercialization of hydrogen for the transportation and energy generation sectors. This study reviews the current trends in hydrogen production, storage, and its applications and their status with reference to India. Infrastructure development, delivery, legislation, cost, and widespread acceptance are all identified as barriers to the commercialization of hydrogen-powered vehicles in India. It further outlines the challenges and techno-economic hurdles in attaining the hydrogen economy.